2007
DOI: 10.1007/s11136-007-9263-8
|View full text |Cite
|
Sign up to set email alerts
|

Respondent satisfaction regarding SF-36 and EQ-5D, and patients’ perspectives concerning health outcome assessment within routine health care

Abstract: Health outcome assessment within routine health care seems to be acceptable, and even appreciated, by patients. Questionnaire length and ease of response were not found to be crucial arguments in choosing between SF-36 and EQ-5D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…243,244,338,339 However, PROMs completion can be an emotional process and the degree to which patients engage with this process may depend on their preferred coping strategy; patients who prefer to deny their current life situation avoid completing PROMs or do not report the true extent of their feelings. 343 We also found evidence to support the theory that completing a PROM signals to the patient that they feel someone is interested in their feelings 81,328,341,343 and this gives them 'permission' to share or raise issues with clinicians. 243,244,338 …”
Section: Theory 10mentioning
confidence: 53%
See 2 more Smart Citations
“…243,244,338,339 However, PROMs completion can be an emotional process and the degree to which patients engage with this process may depend on their preferred coping strategy; patients who prefer to deny their current life situation avoid completing PROMs or do not report the true extent of their feelings. 343 We also found evidence to support the theory that completing a PROM signals to the patient that they feel someone is interested in their feelings 81,328,341,343 and this gives them 'permission' to share or raise issues with clinicians. 243,244,338 …”
Section: Theory 10mentioning
confidence: 53%
“…328 Some patients felt that the 'impersonal' nature of standardised PROMs was helpful in enabling them to share issues with the clinician through PROMs completion. 81 However, others, particularly those with mental health problems, felt that standardised PROMs simply did not capture the complexity or dynamic nature of their symptoms.…”
Section: Theory 12mentioning
confidence: 99%
See 1 more Smart Citation
“…Nilsson et al [40] studied patient satisfaction (n ϭ 463) with the SF-36 and EQ-5D and patients' perspectives regarding health outcome assessment within a routine health-care context. Patients completed the SF-36 and the EQ-5D before and after ordinary interventions.…”
Section: Studies Including Patient Inputmentioning
confidence: 99%
“…The indirect utility instruments EQ-5D, SF-6D and HUI have shown themselves to be feasible as measured by completion time and/or missing data (58,125,144,145), although a recent review in rheumatic diseases (63) showed a high variability in the reports of missing data (from 1 to as much as 40%). Two reviews (63,146) demonstrated a moderate to high test-retest reliability for the EQ-5D.…”
Section: Psychometric Properties Of Direct and Indirect Utility Instrmentioning
confidence: 99%